Synthesis and characterization of 7-hydroxy-4-methylcoumarin-3-ethyl acetate and its derivatives - Lakshmana Bahrathi Satiyamurti, 1995-, author; Joazaizulfazli Jamalis, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018